2003
DOI: 10.1007/s10311-003-0044-5
|View full text |Cite
|
Sign up to set email alerts
|

Organoiodine formation during humification in peatlands

Abstract: Although two billion people in the world are suffering from iodine deficiency there is little information on the chemical fate of iodine in the terrestrial environment. Here we show that peatlands play a major role in terrestrial iodine cycling. Chemical data from two peat profiles from Patagonia, Chile imply that transformation of iodine from its inorganic form to organoiodine compounds during early humification in peatlands is a key process in storage of iodine in the terrestrial environment. Once bound in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 23 publications
1
21
1
Order By: Relevance
“…No I/C data is available from Mississippi River wetlands. However, both ratios appear somewhat higher than reported I/C ratios in peat bogs from Southern Chile (e.g., 1x10 -5 ; Keppler et al, 2004).…”
contrasting
confidence: 62%
See 1 more Smart Citation
“…No I/C data is available from Mississippi River wetlands. However, both ratios appear somewhat higher than reported I/C ratios in peat bogs from Southern Chile (e.g., 1x10 -5 ; Keppler et al, 2004).…”
contrasting
confidence: 62%
“…This has exposed peat deposits with radiocarbon ages of 2000-4000 years, and δ 13 C values of -24.6 to -25 ‰. Keppler et al (2004) found that peatlands sequester large amounts of iodine with average concentrations of 5-36 mg/kg, therefore, one could recognize such layers in a sedimentary record by their unusually high iodine concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Today halogens are known to be involved in a large number of biogeochemical mechanisms related to the transformation of organic matter and some of these processes are basic for the understanding of the biogeochemical cycling of halogens. Natural formation of organohalogens in nearly all aquatic and terrestrial environments is widely accepted to be a key mechanism for the retention and enrichment of halogens in soils (Öberg, 2002) and peatlands (Keppler and Biester, 2003;Biester et al, 2004). Enzymatic processes such as haloperoxidases and halogenases are thought to be the major source of natural halogenated organic compounds in the environment (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Being solely built up by organic matter, they are ideal natural laboratories to study the role of organic matter transformation processes in the biogeochemical cycling of halogens. Data on halogens in peat are still limited to a small number of studies (Chagué-Goff and Fyfe, 1996;Maw and Kempton, 1982;Shotyk, 1997;Silk et al, 1997;Keppler and Biester, 2003;Biester et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation